Literature Study: Analysis of Social Studies Learning in Developing Students’ Character at the Elementary School Level - Ni Luh Ketut Jenutri Sari Devi; I Nyoman Sudirman; Ni Luh Putu Vina Dewi; Ni Komang Ayu Ratnadi; Ni Kadek Wulan Citrawati; Liann Camille Davalos Perez (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
This study aims to analyze and examine Social Studies learning in developing students’ character at the elementary school level. The research employs a qualitative method with a literature review approach. The findings from the literature review indicate that Social Studies learning tends to contribute to the development of elementary school students’ character, particularly when implemented through contextual, participatory, and student-centered learning approaches. Various studies emphasize that IPS content not only provides knowledge about social, cultural, economic, and historical aspects but also encompasses moral and humanitarian values that can be internalized through appropriate teaching strategies. This study is expected to offer a theoretical contribution in the form of a systematic literature synthesis and a practical contribution as a reference for teachers and curriculum developers to optimize the role of IPS as a vehicle for character education in elementary schools.